When persistence pays off [Voices of Africa project] - Watley, Crystal (Technical Centre for Agricultural and Rural Cooperation, 2009)
ICT Update reported on the Voices of Africa project in rural Kenya as part of the web 2.0 issue in October 2007. Despite some difficult times, the project continues to help women farmers in the area.